2006
DOI: 10.1017/s0950268806007205
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis in southern African wildlife: a multi-species host–pathogen system

Abstract: This review examines the current situation of bovine tuberculosis (bTB) in southern African savannah systems, and uses theory on multi-species host-pathogen systems to suggest possible options for future research and management. In southern Africa, the buffalo (Syncerus caffer) and the Kafue lechwe [Marsh antelope] (Kobus leche) have been found to be maintenance hosts for this disease, but the importance of other host species is becoming apparent. The role of other host species in the maintenance and spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
238
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(253 citation statements)
references
References 26 publications
8
238
0
5
Order By: Relevance
“…Previous studies suggested that transmission becomes more frequency-dependent when local transmission is integrated together across spatial scales [37]. In BTB, although many wildlife species can become infected, most of them act as spillover or dead-end hosts, and transmit the pathogen inefficiently [3,6]. The presence of these incompetent hosts might reduce the contact rates among herds by acting as barriers to herd movement, and thus increase the threshold host density and critical community size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that transmission becomes more frequency-dependent when local transmission is integrated together across spatial scales [37]. In BTB, although many wildlife species can become infected, most of them act as spillover or dead-end hosts, and transmit the pathogen inefficiently [3,6]. The presence of these incompetent hosts might reduce the contact rates among herds by acting as barriers to herd movement, and thus increase the threshold host density and critical community size.…”
Section: Discussionmentioning
confidence: 99%
“…As a maintenance host, African buffalo plays an important role in rspb.royalsocietypublishing.org Proc R Soc B 280: 20130624 BTB transmission. Since African buffalo can remain infected and infectious for several years and transmit the pathogen through aerosol transmission [3], this widespread species could limit the efficiency of control measures. The movements of buffalo might also facilitate the spread of the disease, though few studies investigated this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…between buffalo and kudu [40]). Bovine TB epidemiology in wildlife is thus a complex multi-host pathogen system [88], partly driven by resource selection and spatial ecology of wild herbivores sharing common resources and by predator-prey interactions.…”
Section: Conceptual Model Of Btb Transmission At the Wildlife-livestomentioning
confidence: 99%